BIOETIKA DALAM PERSPEKTIF ISLAM SEBAGAI PENGAWAL PERKEMBANGAN BIOLOGI MODERN - Minarno, Eko Budi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Modern biology has been developing so rapidly that the field can amazingly provides great benefits for human beings’ prosperous life either at present or in the future. It may, however, influence the ethical aspects negatively due to reductionism. Therefore, bioethics is highly required to control the devastating growth of modern biology and drive it toward persistent commitment upon human benefits (maslahah). This paper suggests that Bioethics–based learning be implemented in any educational level to develop the students’ critical thinking. Such learning might be put into practice by promoting the ethical decision-making method integrated with religious (Islamic) perspective. The integration would result in the students’ considering the six principles of Islamic bioethics in any modern biology studies so that the students can precisely predict the beneficial or dangerous consequences of their scientific activities.